A Guide to Specimen Management in clinical Microbiology - Miller, J. Michael (ASM Press, 1999)
Provides complete, concise information on the unique needs of the microbiology laboratory regarding specimen management and is the only single source for the specimen management policies required for laboratory results that are accurate, significant, and clinically relevant.